Impact of fat intake on [18F]AlF-NOTA-FAPI-04 uptake in normal abdominal organs - Dai, Jiashun; Zhou, Wanjing; Liu, Huaping; Jiang, Chengzhi; Ye, Hui (Frontiers in Medicine, 2024)
Purpose: [ 18 F]AlF-NOTA-FAPI-04 demonstrates significant physiological uptake in the gallbladder and biliary tract system, representing a limitation of this positron emission tomography(PET) tracer. The aim of this study was to evaluate the impact of milk consumed prior to a PET/CT scan on [ 18 F]AlF-NOTA-FAPI-04 uptake in normal abdominal organs.A total of 86 patients who underwent [ 18 F]AlF-NOTA-FAPI-04 PET/CT imaging took part in this single-center retrospective clinical study at the Hunan Cancer Hospital between December 2020 and August 2021. Patients were divided into two groups according to their pre-PET scan diet: treated group, who consumed 250ml of milk 10±5minutes after the tracer injection, while the control group was permitted no food intake subsequent to the radiotracer administration. The mean standardized uptake value (SUVmean) of gallbladder, liver, small intestine and pancreas were measured in 18 F-FAPI and 18 F-FDG PET/CT.Results: There was a statistically significant difference in the 18 F-FAPI uptake in the gallbladder between the treated group and the control group (P <0.001). The average SUVmean in the treated group was 2.19±2.01 , which was significantly lower than the average SUVmean of 10.04±9.66 in the control group. In the subgroup analysis of patients who underwent paired [ 18 F]FDG and [ 18 F]FAPI PET/CT scans, the 18 F-FAPI uptake of liver and small intestine was significantly lower than the 18 F-FDG uptake in both the treated group and the control group(P <0.001).This study suggests that milk consumption decreases physiological 18 F-FAPI uptake in the gallbladder, potentially enhancing the diagnostic accuracy for gallbladder cancer.